Comparative Analysis of Performance of the Encryption and Decryption Times of Cryptography - Made Yoga Mahardika; Agung Triayudi (CV. Media Digital Publikasi Indonesia, 2024)
Cryptography is the study of mathematical techniques to maintain information security, including the encryption process to protect data and decryption to return it to a readable form. The Rivest Shamir Adleman (RSA) algorithm and Elliptic Curve Cryptography (ECC) are two asymmetric key algorithms that are often used. RSA relies on large number factorization for security, while ECC uses elliptic curves that require more complex computation but are more efficient in resource usage. This study aims to compare the performance of the two algorithms in terms of encryption and decryption time, and analyze efficiency based on various key sizes and data amounts. The research method includes measuring encryption and decryption time with different data inputs using RSA and ECC at various key sizes. Experiments were conducted with data inputs of 128-bit to 512-bit and testing was conducted to measure the speed of each algorithm in the same situation. The results showed that RSA was faster in the encryption process than decryption, while ECC had a faster decryption time than encryption. However, the overall processing time for ECC is longer than RSA, especially when the key size is increased. These results provide insight into the advantages and disadvantages of each algorithm, which can be used as a basis for consideration in selecting algorithms for security applications that require high efficiency.